Deflacjonizm a element normatywny - Witek, Maciej (Filozofia Nauki, 2001)
The author offers a critical analysis of so called deflationary conception of truth. According to the conception in question an adequate theory of truth contains nothing more than instances of a schema: „p” is true iff p. In short, truth is a disquotation. After giving a brief presentation of main deflationary ideas, the author argues that deflationism conflicts with normative epistemology. In other words, being a form of naturalism it leads to elimination of so called normative element from the philosophy of science. For example deflationary conception of truth is not able to account for constitutive connections between normative ideas of truth and reliability.